A Tecnologia Assistiva no contexto das bibliotecas universitárias: soluções assistivas de serviços destinados às pessoas com deficiência - Jesus, Erlani Diogo (Brasil, 2022)
This study aims to propose the implementation of resources in the use of assistive technology (AT) in order to make the products and services offered by university libraries more accessible and inclusive to people with disabilities. In the sections, an approach to the university library was presented within the context of assistive technology. Next, a comment was made on the relationship between the university library and digital culture and the training of teachers and librarians in the 21st century. Thus, the research began, from the mapping of existing products and services in university libraries and, consequently, the execution of the process of identification of inclusive practices for the use of assistive technology. It was investigated how assistive technology can help the work of the librarian. In this perspective, it was about the insertion of actions in the planning for the application of adequate treatments. For this study, a bibliographic research was used, in a qualitative approach, about the accessibility of resources for the use of AT in the reference service of personalized care for PwD. Based on the results, an intensification of continuing education was proposed for work groups, as well as for users with disabilities on adaptive resources; and, the creation of an accessibility policy for the use of assistive technologies within the scope of university libraries. The evaluation of these results became possible from the collaboration (via the online form) of librarians from the libraries of the following federal public institutions: UFAM, UNIFESP, UFF, UFFS, UFMA, UFC, UFSC and UFPE